Fat-talk nation: the human costs of America's war on fat - Greenhalgh, Susan
In recent decades, America has been waging a veritable war on fat in which not just public health authorities, but every sector of society is engaged in constant "fat talk" aimed at educating, badgering, and ridiculing heavy people into shedding pounds. We hear a great deal about the dangers of fatness to the nation, but little about the dangers of today's epidemic of fat talk to individuals and society at large. The human trauma caused by the war on fat is disturbing--and it is virtually unknown. How do those who do not fit the "ideal" body type feel being the object of abuse, discrimination, and even revulsion? How do people feel being told they are a burden on the healthcare system for having a BMI outside what is deemed--with little solid scientific evidence--"healthy"? How do young people, already prone to self-doubt about their bodies, withstand the daily assault on their body type and sense of self-worth? In Fat-Talk Nation, Susan Greenhalgh tells the story of today's fight against excess pounds by giving young people, the campaign's main target, an opportunity to speak about experiences that have long lain hidden in silence and shame. Featuring forty-five autobiographical narratives of personal struggles with diet, weight, "bad BMIs," and eating disorders, Fat-Talk Nation shows how the war on fat has produced a generation of young people who are obsessed with their bodies and whose most fundamental sense of self comes from their size. It reveals that regardless of their weight, many people feel miserable about their bodies, and almost no one is able to lose weight and keep it off.
Keywords: Overweight -- psychology; Young Adult; Personal Narrative